Implementing project portfolio management : a companion guide to the standard for portfolio management - Wu, Te, 1970-; Chatzipanos, Panos A. (Project Management Institute, Inc., 2018)
"The Standard for Portfolio Management - Fourth Edition is a major up- date to the third edition. There are three major changes: 1) The new book is now a principle-based standard in which the applicability has achieved greater universality. 2) The breadth of the new standard is broader, en- compassing a portfolio life cycle, aligning with complexity and system theories, portfolio stakeholder management and portfolio value management. 3) The depth has also been increased to include a section on capability and capacity, a major rework on governance management, and significant insights in value management and stakeholder management. As a principle-based standard, the 'how' of portfolio management is largely removed, and thus, even with a significant addition of concepts and practices, the new standard is nearly 20 percent shorter in length than the previous edition. This is a significant trade-off. To address the 'hows,' select members of the core team decided to work together to write this book, Implementing Project Portfolio Management: A Companion Guide to the Standard for Portfolio Management"--